Enrichment of the Antibiotic Resistance Gene tet(L) in an Alkaline Soil Fertilized With Plant Derived Organic Manure - Peng, Shuang; Dolfing, Jan; Feng, Youzhi; Wang, Yiming; Lin, Xiangui (Frontiers in Microbiology, 2018)
Fifteen antibiotic resistance genes (ARGs) and intI1, a gene involved in horizontal gene transfer of ARGs, were quantified in three different soil samples from a 22 year old field experiment that had received inorganic fertilizer (NPK), organic manure (OM; a mixture of wheat straw, soybean oil cake and cotton cake), and control fields that had received no fertilizer and manure (CK). Tet(L) was the most abundant ARG in OM, which also contained considerable levels of intI1. Molecular analysis of yearly collected archived soils over the past 22 years showed that tet(L) and intI1 were higher in OM soils than in NPK soils. The relative abundance of tet(L) was essentially constant during these years, while the level of intI1 in OM soils decreased over time. The main genotype of tet(L) was the same in archived and in fresh soil, OM and irrigation water. Phylogenetic analysis of the 16S rRNA genes of tetracycline-resistant bacteria isolates indicated that the Firmucutes carrying tet(L) in OM were similar to those in the OM soil, suggesting that OM transferred tetracycline-resistant bacteria into the OM soils where they survived. Almost all of the tetracycline-resistant bacteria isolated from OM carried tet(L) and belonged to the Firmicutes. Survival of bacteria from the organic manure that carried tet(L) may be the cause of the increased level of tet(L) in OM soil.